2018
DOI: 10.1177/1744806918808161
|View full text |Cite
|
Sign up to set email alerts
|

Mouse mast cells and mast cell proteases do not play a significant role in acute tissue injury pain induced by formalin

Abstract: Subcutaneous formalin injections are used as a model for tissue injury-induced pain where formalin induces pain and inflammation indirectly by crosslinking proteins and directly through activation of the transient receptor potential A1 receptor on primary afferents. Activation of primary afferents leads to both central and peripheral release of neurotransmitters. Mast cells are found in close proximity to peripheral sensory nerve endings and express receptors for neurotransmitters released by the primary affer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 75 publications
3
7
0
Order By: Relevance
“…The contribution of MCs to pain via its proteases is also debatable, as they were found not to be essential for acute pain response in the formalin model. 44 Our preclinical findings are supported by a case series of patients with CWP treated with KF, who achieved substantial symptom improvement. This is in line with reports of cases of patients with long-lasting sickle cell anemia pain that improved after the inhibition of MC activation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The contribution of MCs to pain via its proteases is also debatable, as they were found not to be essential for acute pain response in the formalin model. 44 Our preclinical findings are supported by a case series of patients with CWP treated with KF, who achieved substantial symptom improvement. This is in line with reports of cases of patients with long-lasting sickle cell anemia pain that improved after the inhibition of MC activation.…”
Section: Discussionsupporting
confidence: 69%
“…Although the link between NGF and MC activation has been extensively implicated in different models of hyperalgesia, 36 , 39 , 59 , 67 , 80 recent studies have shown that selective depletion of MCs does not reduce NGF-induced peripheral sensitization in vivo, 41 , 44 nor is NGF capable of activating MCs, as they do not express NGF receptors. 41 These studies also showed that CFA-induced mechanical and thermal allodynia 41 and formalin-induced thermal allodynia 44 were not different between selectively MC-depleted and wild-type animals, suggesting that MCs contribute little to the sensitization of peripheral nociceptors. The contribution of MCs to pain via its proteases is also debatable, as they were found not to be essential for acute pain response in the formalin model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken as a whole, the results indicate that MCs play an important role in different painful conditions, although some studies showed that depletion or stabilization of MC did not display pain-relieving effect in models induced by complete Freund’s adjuvant, carrageenan, formalin, NGF, or nociceptin/orphanin (McDougall and Larson, 2006 ; Xanthos et al, 2011 ; Lopes et al, 2017 ; Magnusdottir et al, 2018 ). Whether MC plays a critical role in nociceptive processing remains to be elucidated.…”
Section: Mast Cell Involved In Painful Conditionsmentioning
confidence: 96%
“…NGF treatment in vitro does not lead to increased levels of TNF-α in bone marrow-derived MCs, and qRT-PCR data indicate that MCs express negligible levels of NGF receptors, thereby explaining their lack of response to NGF [ 131 ]. Mouse MCs are not essential to heat hypersensitivity induced by NGF [ 132 ].…”
Section: Neuropeptide Regulation Of Mast Cellsmentioning
confidence: 99%